Integration of Islamic Law and Customary Law on Inheritance (Case Study in Tanjung Pura District, Langkat Regency) - Akmaluddin Syahputra; Khalid Khalid (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This study discusses the integration between Islamic Law and Customary Law in the context of inheritance distribution in Tanjung Pura District, Langkat Regency. With an in-depth case study, this research presents an in-depth understanding of inheritance practices, the role of Islamic Law, and adaptation to local values. The results highlight the alignment of inheritance division with the principles of Islamic Law, while Customary Law also plays a role in shaping the norms that influence this process. It was found that the integration of these two legal systems is manifested in inheritance practices, which reflect tolerance, deliberation, and settlements that consider family values. Nonetheless, disagreements and divergent views on wills and property division were also identified, illustrating the dynamics and complexities of harmonizing these two legal systems. This study contributes to the understanding of how local communities integrate legal and customary aspects in managing inheritance, creating a balance between Islamic norms and local values passed down from generation to generation.